Application of the 2017 criteria for vascular Ehlers‐Danlos syndrome in 50 patients ascertained according to the Villefranche nosology. Issue 2 (3rd November 2019) - Ritelli, Marco; Rovati, Chiara; Venturini, Marina; Chiarelli, Nicola; Cinquina, Valeria; Castori, Marco; Colombi, Marina
Abstract: Vascular Ehlers‐Danlos syndrome (vEDS) is a rare inherited connective tissue disorder due to heterozygous pathogenic COL3A1 variants. Arterial, intestinal, and/or uterine fragility is the disease hallmark and results in reduced life expectancy. The clinical diagnosis is not always straightforward and patients' selection for molecular confirmation depends on the characteristics of applied criteria, that is, the Villefranche criteria (in use until 2017) and their revision according to the new EDS nosology. Herein, we reassessed the clinical features of 50 molecularly proven vEDS patients, diagnosed according to the Villefranche nosology between 2000 and 2016, using the 2017 classification in order to explore its clinical application. Our findings indicate that the Villefranche criteria were particularly valuable for symptomatic patients, even if with a limited specificity. Our study also suggests that the revised vEDS criteria, although expected to be more specific, might have a poorer accuracy, principally in terms of sensitivity. Both sets of criteria are less effective in presymptomatic young patients, especially in the absence of a clear‐cut family history. For these patients, the careful evaluation of the cutaneous, articular, and dysmorphic features and, above all, genetic testing remain crucial to set‐up proper follow‐up and surveillance before catastrophic vascular and intestinal events. Abstract :